THE EFFECT OF DEEP BITE ON POSTURE - Nigmatov R.N.; Bakhshillaeva S.A.; Saidova M.D.; Abdullayeva M.M. (Web of Journals Publishing, 2024)
This article explores the complex relationship between deep bite and posture, shedding light on the potential impact of biting teeth on overall body posture. Using a review and analysis of the literature, this study examines existing data and presents conclusions about the correlation between deep bite and posture changes. The article also discusses the potential implications for dentists and practitioners, providing valuable information for interdisciplinary collaboration.
Keywords: Deep bite, malocclusion, posture, musculoskeletal system, temporomandibular joint (TMJ), dental occlusion, craniofacial morphology.